PERILAKU KEKAKUAN LENTUR PELAT KOMPOSIT LANTAI GABUNGAN BETON PRECAST DAN CAST IN SITU DENGAN PENGKASARAN INTERFACE PADA BEBAN STATIK BERULANG - Agustin Gunawan (Inersia: Jurnal Teknik Sipil, 2019)
The experiment was focused at the midspan part of the slab and conducted to investigate the influence of surface roughing at semi precast slab of the characteristic of elastic of slab made monolithically. In the research, it was conducted testing of two groups of slab which has 1:1 scales. Each group consists of  three. The first group was the monolith slab as control speciment. The second group was the composite slab with surface roughing. Each group was loaded by the repeated center static loading until 10 % of the ultimate load, then the load was taken off. The treatment was carried out 10 time (cycle). The testing result showed that the flexural stiffness of monolith slab and composite width of 400 mm and 600 mm as long as loading 10 was consistent, and the flexural stiffness of slab width of 600 mm was higher than that of slab width of 400 mm. The flexural stiffness increased was not proportion to increased of slab width measurement. At the repeated loading cycle ( 10 cycle), the flexural stiffness of composite slab before P firstcrack reached about 45,21 % (width of 200 mm), 31,70 % (width of 400 mm), and 20,52 % (width of 600 mm) less than that of monolith slab.P first crack